An Economic Analysis of Voting in Sweden - Henrik Jordahl (Uppsala University, Department of Economics, 2001)
This paper presents a theoretical model of rational retrospective voting, which is tested empirically on pooled cross-sectional and panel data from the Swedish Election Studies between 1985 and 1994 supplemented with time series on inflation and unemployment. Compared with the cross-sectional estimates, the panel estimates indicate a relatively greater impact of macroeconomic variables on the individual vote. The principal finding is, however, that microeconomic variables influence the vote about as much as macroeconomic variables do. In consequence, self-interest appears to be an important part of an adequate understanding of economic voting in Sweden. Regarding the determination of election outcomes, macroeconomic variables have been more influential.
Keywords: D72; 330; Elections; voting behavior; pocketbook voting; self-int4erest; public interest; Wahlverhalten; Schweden